Ответ:
а) 6x+12-3x=3x+12=6x-3x+12=3x+12=
3x+12=3x+12=3x+12=3x+12
б) 4x-5-3(2x-10)=
4x-5-6x+30
-2x+25
в)7x-21-4x+15=3x-6
б)4х-5-3*(2х-10)=4х-5-6х+30=-2х+25=-(2х-25)
в)7*(х-3)-(4х-15)=7х-21-4х+15=3х-6=3*(х-2)
Пошаговое объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
а) 6x+12-3x=3x+12=6x-3x+12=3x+12=
3x+12=3x+12=3x+12=3x+12
б) 4x-5-3(2x-10)=
4x-5-6x+30
-2x+25
в)7x-21-4x+15=3x-6
Ответ:
б)4х-5-3*(2х-10)=4х-5-6х+30=-2х+25=-(2х-25)
в)7*(х-3)-(4х-15)=7х-21-4х+15=3х-6=3*(х-2)
Пошаговое объяснение: